Status of medico legal service in Nepal: Problems along with suggestions - Subedi, ND; Deo, S (Journal of College of Medical Sciences-Nepal, 2015)
Forensic medicine deals with the application of medicine for the purpose of law. It is now commonly used to describe all aspects of forensic caseworks; including forensic pathology, that branch of forensic medicine which investigates death, and clinical forensic medicine, which involves interaction between the law, judiciary and the police involving (generally) living persons. The medico legal investigation system in our country still lags far behind the developed countries. The doctors doing the medico legal and post-mortem work at the district level hospitals are often untrained in this sensitive job. It is a job of great responsibility and to leave it to inexperienced doctors is actually doing injustice to the society. Forensic experts handle a very small part of total medico-legal work as most of them work in private medical colleges which are not permitted to handle the work. Mortuaries are housed in outdated facilities. Exposure to the medical students on medico legal cases including autopsy is done only on a sporadic basis taking them to nearby government hospitals and even if they visit the hospitals, inadequate infrastructure prevents better learning. Private medical colleges are conducting postgraduate course in forensic medicine without handling medico legal cases. There should be a post of forensic medicine specialist, at least at the zonal hospitals and the district hospitals handling more medico legal cases. The private medical colleges, especially those enrolling postgraduate students in the field, must seek permission to conduct medico legal works and the government also should not be reluctant in permitting so as it’s not producing adequate experts in itself as per the need of the country. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12769 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 49-54